2021
DOI: 10.1016/j.compbiomed.2021.104944
|View full text |Cite
|
Sign up to set email alerts
|

Detection of COVID-19 from voice, cough and breathing patterns: Dataset and preliminary results

Abstract: COVID-19 heavily affects breathing and voice and causes symptoms that make patients’ voices distinctive, creating recognizable audio signatures. Initial studies have already suggested the potential of using voice as a screening solution. In this article we present a dataset of voice, cough and breathing audio recordings collected from individuals infected by SARS-CoV-2 virus, as well as non-infected subjects via large scale crowdsourced campaign. We describe preliminary results for detection of COVID-19 from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“… [25] Vowel, speech, cough Unique device Unspecified None (76 recovered, 116 total) R, H CNN (transfer learning) Cross-validation 74% (mean, R vs H) Despotovic et al. [24] Vowel, speech, breath, cough Crowdsourced None (self-reported) 84 (1103 total) P, H Adaboost, Multilayer Perceptron, CNN Cross-validation 88% Muguli et al [26] – DiCOVA challenge Vowel, speech, breath, cough Crowdsourced None (self-reported) 60 (990 total) P, H Various Various 73% (baseline) 87% (best) Abbreviations: PCR: Polymerase Chain Reaction-based molecular swab; P: COVID-19 Positive subjects; H: Healthy subjects; R: Recovered subjects; CNN: Convolutional Neural Network; SVM: Support Vector Machine; RNN: Recurrent Neural Network. “Lossless” refers to raw, unprocessed and uncompressed sound data, while “lossy” implies that compression and/or artifacts are present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… [25] Vowel, speech, cough Unique device Unspecified None (76 recovered, 116 total) R, H CNN (transfer learning) Cross-validation 74% (mean, R vs H) Despotovic et al. [24] Vowel, speech, breath, cough Crowdsourced None (self-reported) 84 (1103 total) P, H Adaboost, Multilayer Perceptron, CNN Cross-validation 88% Muguli et al [26] – DiCOVA challenge Vowel, speech, breath, cough Crowdsourced None (self-reported) 60 (990 total) P, H Various Various 73% (baseline) 87% (best) Abbreviations: PCR: Polymerase Chain Reaction-based molecular swab; P: COVID-19 Positive subjects; H: Healthy subjects; R: Recovered subjects; CNN: Convolutional Neural Network; SVM: Support Vector Machine; RNN: Recurrent Neural Network. “Lossless” refers to raw, unprocessed and uncompressed sound data, while “lossy” implies that compression and/or artifacts are present.…”
Section: Discussionmentioning
confidence: 99%
“…[21] obtained an accuracy higher than 90% through principal component analysis (PCA) and data processing using mel-frequency cepstral coefficients (MFCC). The algorithms presented by Pinkas [22] and Shimon [23] yielded average accuracies around 83%, while Despotovic [24] achieved 88% in accuracy considering vocal, speech, cough and breathing crowdsourced sounds. To the best of our knowledge, the only study involving recovered subjects is the one by Suppakitjanusant et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this modality is not useful when the pleura is spared from the pneumonic pathology during the early course of the disease [ 297 ]. Recent developments in the diagnosis of COVID-19 using signals such as respiratory sounds, speech signals, and coughing sounds, have also attracted many researchers [ 298 , 299 ]. Furthermore, in the future, this can be combined with other imaging modalities and signals to enhance the performance of the system using various deep learning approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study investigating the impacts of the disease through voice, analysing the voice before and after infection. According to this study [ 18 ], the detection of COVID-19 through voice by pre-screening method which leads to automatic identification of COVID-19 using analysis of TFR (time frequency representations) with same performance [ 19 ]. presenting dataset for cough, voice, audio recording for breathing gathered form individuals infected by SARS-CoV-2 virus, and also the non-infected subjects as large scale crowd sourced operation.…”
Section: Covid-19 Diagnosis By Signal Processing Of Audio Speech Lang...mentioning
confidence: 99%